Notas sobre la enseñanza del derecho en China contemporánea - Han, Xiaomei (CIAN-Revista de Historia de las Universidades, 2011)
Resumen: Este trabajo tiene como objetivo explicar los cambios que ha sufrido el sistema de enseñanza del Derecho durante el siglo XX en China, desde el final de la sociedad feudal, al germen de la sociedad capitalista y, finalmente, a la época socialista. La forma de la enseñanza del Derecho ha pasado de copiar totalmente la de otros países a buscar la forma adecuada a las circunstancias y al sistema de educación de China. La investigación intenta ofrecer así un análisis de los sucesivos sistemas de enseñanza del Derecho durante el siglo pasado, un acercamiento teórico a los problemas y logros de cada etapa, y una breve reflexión sobre la actualidad. Palabras clave: Enseñanza del Derecho en China, sociedad feudal, sociedad capitalista, sociedad socialista, proceso de la Reforma y Apertura. Abstract: This article describes the changes that took place during the twentieth century on the Chinese legal education, as well as the fundamental influences on each stage of that change. In the last century, China has gone through three different historical stages: the end of the feudal society, the initial phase of the capitalist society, and the socialist society. The legal education has also gone from copying the methods used in foreign countries to finding its own, proper Chinese way to teach law. This research offers an analysis on the changes of the legal education system during that period, a theoretical approach to the problems that that country had and the successes that may have achieved at every stage, and some brief thoughts on the present stage of the question. Key Words: The system of legal education, the feudal society, the capitalist society, the socialist period, the process of Reform and Opening.